210 km long incoherent WDM spectrum-sliced system running at 10 Gb/S incorporating semiconductor optical amplifier (SOA) enhancements - Ian Forsyth, David (Research and Scientific Innovation Society, 2026)
The deployment of more economical and cost-effective wavelength division multiplexing (WDM) solutions for access and metro networks still remains a key research focus. This paper reports on significant performance enhancement improvements of a highly economical, four channel totally incoherent spectrum-sliced WDM system with the incorporation of a Semiconductor Optical Amplifier (SOA) placed in one of its channels. The baseline system was shown to operate well at 10 Gb/s at a maximum link length of 210 km, demonstrating average Q-factor and signal-to-noise ratios (SNRS) over the four channels. However, the introduction of a single saturated SOA and a single filter placed on one channel yielded a sizable improvement in the Q-factor and exceptional improvement in the measured signal-to-noise ratio (SNR), effectively allowing a further 130 km link travel length whilst still yielding acceptable signal quality – making a total link length of 340 km for one channel.